2014
DOI: 10.1093/jis/14.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological responses of the rice leaffolder, Cnaphalocrocis medinalis, to rice plant volatiles

Abstract: The rice leaffolder, Cnaphalocrocis medinalis Guenée (Lepidoptera: Pyralidae), is one of the most destructive pests of rice. Electrophysiological responses of this species to 38 synthetic volatiles known to be released from rice plants (Poaceae: Oryza spp.) were studied using the electroantennogram (EAG) method. Compounds that elicited the strongest EAG responses for each physiological condition were selected for EAG dose-response tests at five concentrations. These compounds included: methyl salicylate, hepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 55 publications
0
21
2
Order By: Relevance
“…Our results demonstrated that the binding activity of CmedOBPs was diverse depending the structure of ligands and interactions of the CmedOBPs. All of the compounds that had high binding activity to CmedOBPs have been showed could elicit high EAG responses in C. medinalis (Sun et al ., ). Furthermore, CmedOBP2 showed high binding activity to host volatiles, whereas CmedOBP3 showed relatively low activity to these volatiles.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Our results demonstrated that the binding activity of CmedOBPs was diverse depending the structure of ligands and interactions of the CmedOBPs. All of the compounds that had high binding activity to CmedOBPs have been showed could elicit high EAG responses in C. medinalis (Sun et al ., ). Furthermore, CmedOBP2 showed high binding activity to host volatiles, whereas CmedOBP3 showed relatively low activity to these volatiles.…”
Section: Discussionmentioning
confidence: 97%
“…A constant flow of 2 l/min of active charcoal air was applied over the antennae through the glass tube. 200 ml/min of air was passed over the filter papers for 0.5 s through the Pasteur pipette, creating odorant stimulation for the antenna (Sun et al ., ). The compound (Z)‐3‐hexenol was used as the reference standard.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…It has been detected in volatiles from a variety of plants, such as Epipogium aphyllum and Acacia cyclops (Fabaccae), as well as the fecal headspace volatiles of Triatoma dimidiata and the Dufour's gland secretions of some ants . Sun et al . found that the volatile nonadecane of rice plants could induce strong EAG responses in female Cnaphalocrocis medinalis , a phytophagous insect.…”
Section: Discussionmentioning
confidence: 99%